Analisis Metode Economic Order Quantity (EOQ) Dalam Pengendalian Rantai Pasok Komponen Mesin Excavator di PT. Anugrah Bangun Makmur - Titong, Fitri Sylvianti; Lutang, Cindy Megavita; Cahyani, Renita; Sakinah, Nur irni Nahri (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
At PT. Anugrah Bangun Makmur, the main problem faced by the company is high inventory costs due to suboptimal ordering frequency and the risk of stock outs and overstocks. Using the EOQ method has a significant impact on cost efficiency and inventory stability. The company's total actual costs of Rp 1,400,677 per year can be reduced to Rp 487,603 after implementing EOQ, resulting in savings of Rp 913,074. In addition, EOQ is also able to reduce the total ordering cost from Rp 300,398 to Rp 246,330. The EOQ method produces a more stable and controlled inventory pattern compared to the company's manual method, so the risk of stockouts and overstocks can be minimized. Overall, the application of the EOQ method has proven effective in improving the efficiency of inventory management at PT. Anugrah Bangun Makmur. This method is able to optimize ordering and storage costs while ensuring the availability of spare parts according to operational needs